Perancangan Penggerak Pada Robot Pemotong Rumput - Azis, Abdul; Irwansi, Yudi; Rahmanda, Dandy (Universitas Semarang, 2023)
The use of robotics to cut grass has been widely used to make it easier and reduce the risk of danger from being hit by cutting blades. Robotic lawn mowers can replace conventional lawn mowers in terms of efficiency and safety in use. In this research, a grass cutting robot will be designed, which will be controlled remotely using a remote control. The drive on the lawn mower robot uses a DC Gearbox motor for forward and reverse movement, a DC Servo motor for turning right and left, and a DC RS 755 motor for movement or to rotate the lawn mower blade. From the results of the tests that have been carried out, the driving performance of the grass cutting robot is in accordance with the design. For forward and reverse movement, the remote control can remotely control the DC Gearbox motor, and the robot lawn mower motor has forward and reverse movement. Where for the forward movement speed of step 1, the speed is 287 rpm - 489 rpm with a torque of 1.1651 Nm - 0.6838 Nm. For step 2 forward movement speed, the speed is 608 rpm - 1,200 rpm with a torque of 0.5500 Nm - 0.2787 Nm. Then for step 1 reverse movement speed, the speed is 432 rpm - 631 rpm with a torque of 0.7741 Nm - 0.5299 Nm. For step 2 reverse movement speed, the speed is 973 rpm - 1,071 rpm with a torque of 0.3437 Nm - 0.3122 Nm. Then for right and left turning movements, the remote control can remotely control the DC Servo motor, and the grass cutting robot has turned right and left. Where for the robot's turning movement to the right and left, step 1 at a speed of 287 rpm - 489 rpm gets a turning angle of 30° with a turning radius of 180°, and step 2 at a speed of 608 rpm - 1,200 rpm gets a turning angle of 20° with a turning radius. 180°. Furthermore, for the movement of the lawn mower blade, the remote control can remotely control the RS 755 DC motor, and the lawn mower blade on the robot rotates. Where for the step 1 grass cutter blade movement speed, the speed is 172 rpm - 229 rpm with a torque of 1.9442 Nm - 1.4602 Nm. For step 2 grass cutter blade movement speed, the speed obtained is 806 rpm - 918 rpm with a torque of 0.4149 Nm - 0.3643 Nm. For step 3 grass cutting blade movement speed, the speed is 976 rpm - 1,147 rpm with a torque of 0.3426 Nm - 0.2915 Nm. Keywords: Mover, Robot, Lawn Mower. ABSTRAK Penggunaan robotika untuk memotong rumput sudah banyak dilakukan untuk memudahkan serta mengurangi resiko bahaya terkena pisau pemotong. Robot pemotong rumput dapat menggantikan mesin potong rumput konvensional dalam hal efisiensi serta keamanan dalam penggunaaan. Pada penelitian ini akan dirancang penggerak robot pemotong rumput, yang dikendalikan yang dikendalikan dari jarak jauh menggunakan remote control. Penggerak pada robot pemotong rumput menggunakan motor DC Gearbox untuk gerakan maju dan mundur, motor DC Servo untuk gerakan belok ke kanan dan ke kiri, dan motor DC RS 755 untuk gerakan atau untuk memutar pisau pemotong rumput. Dari hasil pengujian yang telah dilakukan, kinerja penggerak pada robot pemotong rumput sesuai dengan perancangan. Untuk gerakan maju dan mundur, remote control dapat mengendalikan dari jarak jauh motor DC Gearbox, dan robot pemotong rumput motor telah bergerak maju dan mundur. Dimana untuk kecepatan gerakan maju step 1 didapatkan kecepatan 287 rpm - 489 rpm dengan torsi 1,1651 Nm - 0,6838 Nm. Untuk kecepatan gerakan maju step 2 didapatkan kecepatan 608 rpm - 1.200 rpm dengan torsi 0,5500 Nm - 0,2787 Nm. Kemudian untuk kecepatan gerakan mundur step 1 didapatkan kecepatan 432 rpm - 631 rpm dengan torsi 0,7741 Nm - 0,5299 Nm. Untuk kecepatan gerakan mundur step 2 didapatkan kecepatan 973 rpm - 1.071 rpm dengan torsi 0,3437 Nm - 0,3122 Nm. Kemudian untuk gerakan belok ke kanan dan ke kiri, remote control dapat mengendalikan dari jarak jauh motor DC Servo, dan robot pemotong rumput telah belok ke kanan dan ke kiri. Dimana untuk gerakan belok ke kanan dan ke kiri robot step 1 saat kecepatan 287 rpm - 489 rpm didapatkan sudut belok 30° dengan radius putar 180°, dan step 2 saat kecepatan 608 rpm - 1.200 rpm didapatkan sudut belok 20° dengan radius putar 180°. Selanjutnya untuk gerakan pisau pemotong rumput, remote control dapat mengendalikan dari jarak jauh motor DC RS 755, dan pisau pemotong rumput pada robot telah berputar. Dimana untuk kecepatan gerakan pisau pemotong rumput step 1 didapatkan kecepatan 172 rpm - 229 rpm dengan torsi 1,9442 Nm - 1,4602 Nm. Untuk kecepatan gerakan pisau pemotong rumput step 2 didapatkan kecepatan 806 rpm - 918 rpm dengan torsi 0,4149 Nm - 0,3643 Nm. Untuk kecepatan gerakan pisau pemotong rumput step 3 didapatkan kecepatan 976 rpm - 1.147 rpm dengan torsi 0,3426 Nm - 0,2915 Nm.